Determination of Elastic Constants in WC/Co Metal Matrix Composites by Resonant Ultrasound Spectroscopy (RUS) and Impulse Excitation - Koopman, M.; Chawla, K.K.; Coffin, C.; Patterson, B.R.; Deng, X.; Patel, B.V.; Fang, Z.; Lockwood, G. (Advanced engineering materials, 2002)
Elastic moduli were determined by impulse excitation and resonant ultrasound spectroscopy (RUS) techniques for composite systems of WC/Co. Two types of composites were used, including a novel microstructure termed “double cemented carbides” consisting of WC/Co granules in a Co matrix, as well as a conventional isotropic WC/Co. The results compared favorably with theoretical values predicted by the bounds of the Hashin‐Shtrikman equations for quasi‐isotropic materials. Various aspects of the RUS and impulse excitation techniques are discussed, particularly in regard to composite materials.